Pengabdian Masyarakat Melalui Kegiatan Bakti Literasi Berbasis Inklusi Sosial Di Desa Jaring Halus Kabupaten Langkat - Muhammad Arifin; R Rudianto; R Radiman; Wirda Rizky Anggiani; Putri Febria Liza (Jurnal TUNAS, 2022)
Community service is the process of implementing the knowledge learned in higher education in order to provide the widest possible benefit to the community. Community service activities must always be directed at activities whose benefits and impacts can be felt by the community directly. One form of service that can be done is in the form of literacy services. Therefore, through this literacy service, by visiting Jaring Halus Village, Langkat Regency with the aim of providing motivation to children in Jaring Halus Village so that they can continue to study until college. This activity is a collaboration between the University of Muhammadiyah North Sumatra Library and the Volunteer Library of the University of Muhammadiyah North Sumatra. The form of activities carried out in the form of training on technology, socialization of learning motivation, writing essays in the form of short stories, and competitions related to literacy.